2017
DOI: 10.35808/ersj/807
|View full text |Cite
|
Sign up to set email alerts
|

Types of Financial and Credit Products: Concept, Subject, and Place on Russian and Global Financial Market

Abstract: The paper reveals essential features of financial and credit products as inherent components of Russian and global financial market, which is driven by current global economy integration trends. Financial market is highlighted to provide economic security and proper environment for individuals and legal entities. Taking structural fluctuations in consuming credit products as well as product extension, authors dip into this financial market segment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In the course of the study, considerable attention was paid to the approaches revealed in the works of Gronroos (1982), Deming (1994), McDougall and Levesque (2000), Lee (2000), Babich et al (2015), Japparova and Rupeika-Apoga (2017). Various aspects of the banking theory were studied on the basis of the research of Russian economists such as Seitkassimov and Mussina (2012), Mitrokhin et al (2016), Gubin et al (2017) and Albekova (2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the course of the study, considerable attention was paid to the approaches revealed in the works of Gronroos (1982), Deming (1994), McDougall and Levesque (2000), Lee (2000), Babich et al (2015), Japparova and Rupeika-Apoga (2017). Various aspects of the banking theory were studied on the basis of the research of Russian economists such as Seitkassimov and Mussina (2012), Mitrokhin et al (2016), Gubin et al (2017) and Albekova (2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…127-FZ (1996) (hereinafterthe Law "On Science"), which consolidates the powers of state authorities in the relevant sphere as the main aspects of management of scientific activity. It is also stated that within their powers the bodies of the state authorities of the Federation, its subjects and state academies of sciences determine the relevant priority areas for the development of science and technology, ensure the formation of a system of scientific organizations, implementation of inter-industry coordination of scientific and (or) scientific and technical activities, development and implementation of scientific and technical programs and projects, development of forms of integration of science and production, realization of the achievements of science and technology (Dmitrishina and Uskov, 2015;Ivanova et al, 2017;Gubin et al, 2017).…”
Section: The Powers In the Management Of Science And Determination Ofmentioning
confidence: 99%
“…Prospects and limitations of small business are explored in several countries (Rahman et al, 2010;Carstina et al, 2015;Gubin et al, 2017). Many authors note that different approaches to the selection of sources of financing are used, but there is no mechanism for sound financing management that positively influences performance indicators.…”
Section: Introductionmentioning
confidence: 99%